Reviving the Sanghyang Grodog Ritual Dance: Promoting Social Harmony and Sustainable Cultural Tourism in Nusa Lembongan Island, Bali - Ni Made Arshiniwati; Ida Bagus Gede Surya Peradantha (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This article explores the artistic significance and revitalization of the Sanghyang Grodog ritual in Lembongan Village, Bali, following a three-decade hiatus. Using a socio-artistic approach supported by social cohesion and semiotic theories, this study examines the ritual’s role in fostering social identity and promoting sustainable, culture-based tourism. Data were collected through participant observation, interviews, and secondary sources, with findings reinforced by focus group discussions. The results highlight the ritual’s embodiment of spiritual, social, and environmental harmony while addressing challenges posed by increasing tourism pressure. Despite limited public awareness, the ritual’s aesthetic and symbolic values serve as a catalyst for communal unity and sustainable cultural tourism. This study proposes a community-based tourism development strategy that includes the creation of a local mascot, visual branding, and the integration of arts into ecotourism and education, ensuring both cultural preservation and economic benefits for the community.